The Role of Nur ad-Din Zanki in Establishing the Sunni School in Aleppo and Damascus in 1146-1174 AD - Ibnu, Muhammad Iqbal (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
This scientific work is entitled Sunni Educational Institutions in Aleppo and Damascus during Nuruddin Zanki's Period, 1146-1174 CE. This historical study takes the time span of 1146-1174 CE. Because during this period, which concided with Nuruddin Zanki's leadership, Sunni Educational Institutions began massive and spread throughout Aleppo and Damascus. The results of the writing of this scientific paper conclude that: during the reign of Nuruddin Zanki, many Sunni-based educational institutions were established which had the function of overcoming the influence of the Imami and Ismaili Shia as well as the Sunni approach in the people of Aleppo and Damascus. Among the educational institutions scattered in Aleppo and the Damascus Madrasa based on four schools of jurisprudence, namely Syafi'i, Hanafi and some Hambali and Maliki, Dar-Al-Hadith, Zawiyah.Keywords: Nuruddin Zanki, Sunni Madhhab, Shi’a Madhhab.